2015
DOI: 10.1002/rcm.7253
|View full text |Cite
|
Sign up to set email alerts
|

Rb‐Sr resonance ionization geochronology of the Duluth Gabbro: A proof of concept forin situdating on the Moon

Abstract: RationaleWe report new 87Rb‐87Sr isochron data for the Duluth Gabbro, obtained with a laser ablation resonance ionization mass spectrometer that is a prototype spaceflight instrument. The gabbro has a Rb abundance and a range of Rb/Sr ratios that are similar to those of KREEP‐rich basalts found on the nearside of the Moon. Dating of previously un‐sampled young lunar basalts, which generally have a KREEP‐rich composition, is critical for understanding the bombardment history of the Moon since 3.5 Ga, which in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 50 publications
(77 reference statements)
1
25
0
Order By: Relevance
“…Other authors reported similar issues and mostly attributed the source of the distortions to a lack of shot‐to‐shot stability of the ablation laser . In particular, when Q‐switched lasers (eg, Nd:YAG laser operating in the ns pulse range) are used, the shot‐to‐shot fluctuations of the pulse are commonly in the range of a few percent, but values high as 40% were measured in our previous measurements .…”
Section: Introductionsupporting
confidence: 52%
“…Other authors reported similar issues and mostly attributed the source of the distortions to a lack of shot‐to‐shot stability of the ablation laser . In particular, when Q‐switched lasers (eg, Nd:YAG laser operating in the ns pulse range) are used, the shot‐to‐shot fluctuations of the pulse are commonly in the range of a few percent, but values high as 40% were measured in our previous measurements .…”
Section: Introductionsupporting
confidence: 52%
“…() and Anderson et al. () for Mars and the Moon respectively, has the potential to calibrate model ages for other solar system bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a significant advance in our understanding of the crater chronology could be made with lunar samples returned from several locations bridging this time period. Furthermore, development of in situ dating such as discussed by Farley et al (2014) and Anderson et al (2015) for Mars and the Moon respectively, has the potential to calibrate model ages for other solar system bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Radiometric dating of returned samples is the most straightforward way to identify formation ages as well as overprinting episodes associated with major impacts, but recent advances have now also demonstrated in situ age dating [ Farley et al ., ]. Multiple instruments designed and optimized specifically for age dating have been developed for flight [ Farley et al ., ; Cohen et al ., ; Solé , ; Anderson et al ., , ; Cho et al ., ] opening up the possibility for missions to carry payload elements designed to both elucidate the Martian planetary chronology and give solar system‐wide context to Mars' geochemical change with stratigraphy as it is explored.…”
Section: Mars As a Linchpin For Terrestrial Evolution: Requirements Fmentioning
confidence: 99%